Effect of mixed acid catalysis on pretreatment and enzymatic digestibility of sugar cane bagasse - Pal, Siddhartha; Joy, Shereena; Kumbhar, Pramod; Trimukhe, K. D.; Varma, Anjanikumar; Padmanabhan, Sasisanker (Energy & Fuels, 2016)
Aqueous pretreatment using homogeneous acid catalyst is considered as a low-cost technology in the production of lignocellulosic bioethanol. To establish the synergism of mixed acids, pilot-level aqueous pretreatments of bagasse covering a wide range of combined severity (CS) were carried out. To investigate the effect of application of mixture of acids on xylose hydrolysis as well as glucose hydrolysis via pretreatment and enzymatic hydrolysis, the following three combinations of acids were explored: (1) oxalic acid + sulfuric acid (organic + mineral acid), (2) phosphoric + sulfuric acid (mineral acids), and (3) ferric chloride + sulfuric acid (Lewis acid with a mineral acid). Of the pretreatments evaluated, the synergism was most pronounced for the combination of sulfuric and phosphoric acid, which resulted in more than 90% conversion of hemicellulose to xylose and 70% conversion of cellulose to glucose through enzymatic hydrolysis. Fourier transform infrared (FTIR) studies of pretreated samples showed higher syringyl/guaiacyl (S/G) ratio for sulfuric and phosphoric acid combination pretreatment, leading to higher enzymatic conversion. FTIR and dynamic light scattering (DLS) experiments conducted on pretreated sugar cane bagasse provided useful correlation with regard to the pretreatment type, particle size, and enzymatic hydrolysis.

Pretreatment and enzymatic process modification strategies to improve efficiency of sugar production from sugarcane bagasse - Pal, Siddhartha; Joy, Shereena; Trimukhe, Kalpana D.; Kumbhar, Pramod S.; Varma, Anjani J.; Padmanabhan, Sasisanker (3 Biotech, 2016)
Pretreatment and enzymatic hydrolysis play a critical role in the economic production of sugars and fuels from lignocellulosic biomass. In this study, we evaluated diverse pilot-scale pretreatments and different post-pretreatment strategies for the production of fermentable sugars from sugarcane bagasse. For the pretreatment of bagasse at pilot-scale level, steam explosion without catalyst and combination of sulfuric and oxalic acids at low and high loadings were used. Subsequently, to enhance the efficiency of enzymatic hydrolysis of the pretreated bagasse, three different post-pretreatment process schemes were investigated. In the first scheme (Scheme 1), enzymatic hydrolysis was conducted on the whole pretreated slurry, without treatments such as washing or solid-liquid separation. In the second scheme (Scheme 2), the pretreated slurry was first pressure filtered to yield a solid and liquid phase. Following filtration, the separated liquid phase was remixed with the solid wet cake to generate slurry, which was then subsequently used for enzymatic hydrolysis. In the third scheme (Scheme 3), the pretreated slurry was washed with more water and filtered to obtain a solid and liquid phase, in which only the former was subjected to enzymatic hydrolysis. A 10 % higher enzymatic conversion was obtained in Scheme 2 than Scheme 1, while Scheme 3 resulted in only a 5-7 % increase due to additional washing unit operation and solid-liquid separation. Dynamic light scattering experiments conducted on post-pretreated bagasse indicate decrease of particle size due to solid-liquid separation involving pressure filtration provided increased the yield of C6 sugars. It is anticipated that different process modification methods used in this study before the enzymatic hydrolysis step can make the overall cellulosic ethanol process effective and possibly cost effective.
Keywords: Dilute acid treatment; High-solid enzymatic hydrolysis; Pilot-scale pretreatment; Pressure filtration; Solid-liquid separation

Pilot-scale pretreatments of sugarcane bagasse with steam explosion and mineral acid, organic acid, and mixed acids: synergies, enzymatic hydrolysis efficiencies, and structure-morphology correlations - Pal, Siddhartha; Joy, Shereena; Kumbhar, Pramod S.; Trimukhe, Kalpana D.; Gupta, Rishi; Kuhad, Ramesh Chander; Varma, Anjani J.; Shankar, Sasi (Biomass Conversion and Biorefinery, 2017)
In lignocellulosic (LC) ethanol processes, to facilitate enzymatic hydrolysis of cellulose, a physical chemical pretreatment is vital. In this study, we explored a single as well as a two-step physical-chemical pretreatment involving steam and mixed acid on unwashed sugarcane bagasse at pilot-scale level in a continuous horizontal reactor. To serve as a large-scale model, pretreatments were carried out at high solid levels of 18–20 % w/w. For the pretreatment, partial replacement of corrosive sulfuric acid with a milder acid-like oxalic acid was explored to derive possible advantages and synergies accruing by using a mixture of mineral acid and organic acid. The results of this work showed that first-step pretreatment carried out by the mixing of sulfuric acid (1.5 % w/w) and oxalic acid (1.5 % w/w) at 150 °C followed by a second-step steam explosion pretreatment at 180 °C gave significant synergies and advantages over other variants of pretreatments investigated, such as lower inhibitor levels and lower reaction severity. On post-pretreated bagasse, this study conducted comparative enzymatic hydrolysis study using a simple lab enzyme and a robust commercial enzyme. It was found that the addition of Tween 80 to the lab enzyme improved its performance to match the performance of the commercial enzyme. Scanning electron microscopy (SEM) studies were further carried out to correlate the morphology of pretreated samples with efficiency of enzyme hydrolysis. Besides morphological study, Fourier transform infrared (FTIR) studies of pretreated samples showed higher syringyl/guaiacyl ratio for all pretreatments, indicating lower levels of pseudo-lignins, which is beneficial for improved enzyme hydrolysis.